1997
DOI: 10.1055/s-2008-1080157
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Interstitial Laser Photocoagulation of Bones

Abstract: Interstitial laser photocoagulation (ILP) was performed in experimental models prior to clinical trials to determine the feasibility of bone photocoagulation using an 805-nm diode laser and to define parameters influencing lesion size and shape. Laser energy was applied in continuous-wave mode at a power of 2 W to an ex vivo freshly ablated pig femur. Two hundred and eighty ILPs were performed followed by histologic examinations to determine the coagulation size with a freshly cleaved fiber tip compared to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…However, following Gangi et al [19][20], we believe that laser photocoagulation has some advantages over radiofrequency ablation. With laser therapy, coagulation and tissue destruction starts from the probe, which is acting as a point heat source and radiates from the center to the periphery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, following Gangi et al [19][20], we believe that laser photocoagulation has some advantages over radiofrequency ablation. With laser therapy, coagulation and tissue destruction starts from the probe, which is acting as a point heat source and radiates from the center to the periphery.…”
Section: Discussionmentioning
confidence: 93%
“…A lowpower laser beam (2 W) was emitted by a 15-W laser generator (Stryker, Kalamazoo, MI), at 2 W per second. Based on the data from Gangi et al [20], we provided an energy of at least 100 J for 1-mm-size nidus. However, in order to minimize the risk of recurrence, in deep bone lesions distant from neurovascular bundles and joints, or in case of suboptimal placement of the laser fiber, the delivered laser energy was generally increased and could even reach 2,000 J (two patients).…”
Section: Methodsmentioning
confidence: 99%
“…11 Attempts to overcome this problem have led to the development of numerous methods of allowing accurate intraoperative localization of the nidus. 14,15 Laser photocoagulation as a method for treating osteoid osteomas was first described by Gangi et al 6,17 The same author reported a series of 114 Osteoid osteomas.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Experimental studies have shown a good correlation between the energy delivered and the size of the lesion. 21 In the femur of the pig, the mean axial diameter of coagulation with a constant power of 2 W varied from 3.4 mm with 200 J to 9.2 mm at 1000 J. The longitudinal diameter of coagulation along the fibre track was greater than the axial diameter with 4 mm at 200 J and 11.1 mm at 1400 J.…”
Section: 15mentioning
confidence: 99%